Actuality of Life of Gerasim Zelić - Evidence of a Time and/or Lesson for the Future - Ernaut, Miloš (Sociološki godišnjak, 2023)
Gerasim Zelić (1752-1828), archimandrite of the Krupa Monastery in Dalmatia, was one of the most famous Serbs of his time and a great traveler. The only written trace of his many travels is the autobiography of the Life of Gerasim Zelić. In that work, he describes important political events throughout Europe, the Middle East and Russia, which he witnessed or directly participated in. His analytical and storytelling gift presented in the Life of Gerasim Zelić is a good basis for understanding the political relations between the East and the West at the time, but also the wider context through which the similarities and differences between the mentioned cultural circles were interwoven. In this sense, the goals of this research are synchronic and diachronic. In the first case, we will try to present and critically analyze Zelić’s perception of the events he describes as their contemporary. At the same time, we will try to determine the current relevance of his insights presented in the aforementioned work. We will approach the analysis of the mentioned work through an appreciation of the hermeneutic perspective, i.e. appreciation of the mutual relationship between the past and the present. The results of our research indicate that the Life of Gerasim Zelić is a work that transcends the framework of the time in which it was created, because the context of mutual (mis)understanding of East and West has not changed since then.